(untitled) (CAHIERS MAGELLANES-NS, 2024)
This article explores the significant impact of Christian missions on social transformation in the North Arcot region. Over the years, Christian missions have played a crucial role in reshaping various aspects of societal structure and cultural dynamics in this area. This research examines how these missions have influenced social change through their educational, healthcare, and welfare initiatives. By analyzing historical data, mission records, and contemporary accounts, the study highlights the extent to which Christian missions have contributed to social development, including advancements in literacy, healthcare accessibility, and the empowerment of marginalized communities. The findings underscore the complex interplay between religious missions and social progress, offering insights into faith-based organizations can drive systemic change in diverse cultural contexts.